Bridging the urban divide between the informal and the planned city. The African microstate of São Tomé and Príncipe as case-study. - Ana Silva Fernandes (2012)
The worldwide acceleration of the urbanisation process in the last decades has induced great pressure in the urban built environment, especially in developing countries, where this growth could not be met by similar provision of support structures, thus creating extensive disparities and informal settlements. This has happened in megacities, but also in their smaller counterparts. Focusing on the case-study of São Tomé and using the data collected during research and fieldwork, this paper will present an analysis of the urbanisation process, its heterogeneity and its spatial repercussions of unbalanced distribution of public space and dwelling conditions. These will contribute to the discussion of options for challenging these disparities within the urban built environment, their misconceptions and disarticulations, namely the role of planning, design and stakeholders as catalysers for development.